Missed Diagnosis of Phyllodes Tumour And Its Implications - A Case Report - Das, Prosunto Kumar; Rahman, AZM Mahfuzur; Sina, Md Nayeem Dewan; Mamun, Abu Masud Al (Journal of Dhaka Medical College, 2021)
Phyllodes tumours are rare fibroepithelial tumours that accounts for less than 1% of all breast tumours. Phyllodes tumours tend to grow quickly but they rarely spread outside the breast. Although most phyllodes tumours are benign, some are malignant and some are borderline. It is often underdiagnosed by pathologists and under treated by surgeon. Its heterogenicity makes phyllodes tumour a challenge for the clinicians and the pathologists. Accurate preoperative diagnosis by Fine Needle Aspiration Cytology or by Core biopsy or peroprative diagnosis by Frozen section biopsy is essential for adequate surgical treatment. This case describes a missed diagnosis of phyllodes tumour both by cytopathologically and histopathologically. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 182-184